THE REPRESENTATION OF EDUCATIONAL AND CULTURAL VALUES IN THE NOVEL NEGERI 5 MENARA BY AHMAD FUADI: A STUDY OF CHILDREN'S AND YOUNG ADULT LITERATURE - Afni Rosalina, Ratna Sari Dewi (LP2M Universitas Muslim Nusantara Al Washliyah, 2026)
The aim of this study is to explore how cultural and educational values are represented in the book Negeri 5 Menara and how these values can be applied to literature for young adults and children. The novel portrays the educational journey of the main character at Pondok Madani, a place where important values like self-control, hard work, perseverance, and religious devotion are taught. Through the backgrounds of its characters, who come from various regions, as well as the traditions of Islamic boarding schools that shape their identities, the book also highlights Indonesia's cultural diversity. This research employs a literature review and content analysis of the novel to gather data, using a qualitative descriptive-analytical approach. The results indicate that the cultural and educational values embedded in the novel have a significant impact on the development of young readers as individuals